Being close to a cow - Säfström, Ida (2019)
The purpose of this thesis is to explore learning in farming environments from a perspective of bodily experience. The aim is to create understanding about the role of bodily experience in learning the craft of farming. I want to shed light on what kind of understandings that being mentally and physically close to animals, things and people involved in farming environments can generate. The study is based on participant observation among eleven high school students in their second year at an Agricultural program in Rättvik, Sweden. The students’ statements, stories and daily practices, combined with my own experiences of being there, both as a visitor and as a participant, form the basis of the result. It shows how shared bodily experience can generate a sense of belonging and togetherness. It shows how bodily experience in farming environments, which are related to what you have chosen to learn, creates feelings of doing something that matters and is meaningful. The teachers and students I met turn their school into a place where practice and bodily experience is allowed to play a vital part in processes of learning. This thesis also illuminate how closeness to animals, people and things involved in learning processes in farming environments can enhance feelings of care, responsibility and understandings of what it is like to be with the world.